El pleuston de Pistia stratiotes de la laguna Barranqueras (Chaco, Argentina) - Neiff, Alicia Poi; Neiff, Juan José (Ecosur, 2025)
A floating carpet of Pistia stratiotes in the “Barranqueras” pond (near Paraná river) has been studied in their vegetation and faunal composition during the period October, 1974 to December, 1975 by monthly sampling operations. The samples were collected in several points along the main radial section by mean a special circular sampler with 32 cm diameter. In the freíd operations, also were taken structural data of vegetal population, like density, plant size, growth phases, and general fenology, recording at the same time the most interesting limnological parameters. In the laboratory, the animáis were removed by washing the vegetation in sieves of different size, followed by Berlese funnel treatment. The material was identified at the best posible systematic level, estimating the numerical density and the biomass. The population of aquatic invertebrates associated with Pistia stratiotes varied between 3200 and 18000 organisms/m^, and the standing crop was less than 4,45 g/m2 (dry weigth). The result did not exceed 21,5 g/m2 including the macrofauna. The vegetal biomass fluctuate between 394 and 166 g/m^ (dry weigth) According to the data obtained, the mesofauna never reach 5 o/o of the total vegetal biomass, attaining a maximun of 8 o/o if the macrofauna are considered.